2020
DOI: 10.1371/journal.pone.0236432
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prevalence of multiple sclerosis in Hungary based on record linkage of nationwide multiple healthcare administrative data

Abstract: Objectives As there were only regional studies in Hungary about the prevalence of multiple sclerosis (MS), we aimed to estimate its epidemiological features using data of Hungary's singlepayer health insurance system. Methods Pseudonymized database of claims reported by hospitals and outpatient services between 2004-2016 was analyzed and linked with an independent database of outpatient pharmacy refills between 2010-2016. We established an administrative case definition of MS and validated it on medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
(85 reference statements)
1
11
0
4
Order By: Relevance
“…The previous examination of the same geographical location we surveyed in our current work the male:female ratio was found to be 1:2.75 and 1:3.08 in the MS population and 1:1.09 and 1:1.12 in the overall county population in 1999 and 2013, respectively [72,76]. Our findings of the continuous rise in the prevalence and female:male ratio of MS are in accordance with both current international and national findings in the literature [28,75,[77][78][79]. Even though many theories [78] have seen the light in the past decades trying to explain the tendency (most of which are valid for Hungary as well), no unequivocal explanation for this rise in prevalence has been born yet.…”
Section: Fresh Epidemiological Data Based On the Novel Phenotypic Classification And Treatment Statussupporting
confidence: 90%
See 1 more Smart Citation
“…The previous examination of the same geographical location we surveyed in our current work the male:female ratio was found to be 1:2.75 and 1:3.08 in the MS population and 1:1.09 and 1:1.12 in the overall county population in 1999 and 2013, respectively [72,76]. Our findings of the continuous rise in the prevalence and female:male ratio of MS are in accordance with both current international and national findings in the literature [28,75,[77][78][79]. Even though many theories [78] have seen the light in the past decades trying to explain the tendency (most of which are valid for Hungary as well), no unequivocal explanation for this rise in prevalence has been born yet.…”
Section: Fresh Epidemiological Data Based On the Novel Phenotypic Classification And Treatment Statussupporting
confidence: 90%
“…Based on our current findings and previous epidemiological data from the same region Hungary is still considered a medium-risk country for MS [69][70][71][72][73][74] from an international perspective. A most recently published retrospective study from Hungary [75] with the prevalence day set in 2015 has found a slightly higher prevalence they reported a cumulative standardized of 127.2/100,000 (175.6 for women and 74.7/100,000 for men), found the male:female ratio to be 1:2.6, observed a cumulative incidence of 5.1/100,000 (7.1/100,000 for women, 3.1/100,000 for men). A plausible explanation for the difference between the results of the two studies may be the differences in patient selection and the quality of the data on which the studies were based.…”
Section: Fresh Epidemiological Data Based On the Novel Phenotypic Classification And Treatment Statusmentioning
confidence: 99%
“…Several MS case-finding algorithms to identify patients from administrative databases have been published both in Italy [12] and in other countries in Europe [21-23] or North America [20, 24, 25]. While comparisons between algorithms from different health systems are difficult because of differences in data recording, our algorithm uses the same data sources as others validated in Italy, with similar or better sensitivity.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Mivel ez a szűrés nem eléggé specifikus -hiszen olyanok is szerepelnek benne, akik például egyetlen laborvizsgálathoz kaptak sclerosis multiplex diagnózisú kódot -, a nemzetközi példákat -elsősorban Marrie [13] és Culpepper munkásságát [17,18] -alapul véve és adaptálva létrehoztuk a sclerosis multiplex "adminisztratív definícióját" [19]. E szerint azt a személyt tekintjük sclerosis multiplexesnek, aki az alábbi három kritérium mindegyikét teljesíti a vizsgált időszakban: -legalább három különböző dátummal kapott G35-ös diagnóziskódot (akár elsődleges, akár kísérő betegségként, fekvő vagy járó betegként), de nem véve figyelembe a laboratóriumi, képalkotó és patológiai vizsgálatok során adott diagnózisokat, mivel azok gyakran csak iránydiagnózisok; -a diagnózis megerősítésének tekintettük, hogy a beteghez regisztrált G35-ös kódok legalább egyikét neurológus adta, azaz neurológiai osztályos bennfekvés során vagy neurológiai jellegű szakrendelésen rögzítették; -a G35-ös kódokat legalább két különböző (nem feltétlenül egymást követő) naptári évben kapta a beteg, ezzel igyekezve kiszűrni azokat, akiket sclerosis multiplex irányában vizsgáltak, és végül ez a diagnózis nem igazolódott.…”
Section: Módszerekunclassified